Unraveling overestimated exposure risks through hourly ozone retrievals from next-generation geostationary satellites - Siwei Li; Ge Song; Jia Xing; Jiaxin Dong; Maolin Zhang; Chunying Fan; Shiyao Meng; Jie Yang; Lechao Dong; Wei Gong (Nature Communications)
Abstract Accurate ground-level ozone (O3) estimation is crucial for assessing health impacts and designing control strategies. Traditional polar-orbit satellites provide limited, one-time measurements, missing O3’s diurnal variability. Here, we utilize a next-generation geostationary satellite with ultraviolet capabilities to retrieve hourly O3 concentrations, achieving high accuracy (R2 = 0.94) and improving daily maximum 8-hour estimates, particularly in semi-urban areas (R2 + 0.10, error reduction >7 μg/m³). Our analysis reveals a 30% drop in O3-related health risks compared to traditional polar-orbit estimates, with the greatest impact in semi-urban and rural areas where satellite data plays an important role due to the lack of ground measurements. This suggests prior estimates may have overestimated total mortality and urban-rural spillover effects. Our findings underscore the importance of geostationary satellites in capturing O3 diurnal variability through refined hourly data on photochemical precursors and radiation, providing a scientific basis for health assessments and informing O3 pollution regulations in China.